Somatosensory Testing in Pediatric Patients with Chronic Pain: An Exploration of Clinical Utility - Anna Kersch; Panchalee Perera; Melanie Mercado; Andrew Gorrie; David Sainsbury; Tara McGrath; Phillip Aouad; Sara Sarraf; Tiina Jaaniste; David Champion (MDPI AG, 2020)
We aimed to evaluate the utility of clinical somatosensory testing (SST), an office adaptation of laboratory quantitative sensory testing, in a biopsychosocial assessment of a pediatric chronic somatic pain sample (N = 98, 65 females, 7-18 years). Stimulus-response tests were applied at pain regions and intra-subject control sites to cutaneous stimuli (simple and dynamic touch, punctate pressure and cool) and deep pressure stimuli (using a handheld pressure algometer, and, in a subset, manually inflated cuff). Validated psychological, pain-related and functional measures were administered. Cutaneous allodynia, usually regional, was elicited by at least one stimulus in 81% of cases, most frequently by punctate pressure. Central sensitization, using a composite measure of deep pressure pain threshold and temporal summation of pain, was implied in the majority (59.2%) and associated with worse sleep impairment and psychological functioning. In regression analyses, depressive symptoms were the only significant predictor of pain intensity. Functional interference was statistically predicted by deep pressure pain threshold and depressive symptoms. Manually inflated cuff algometry had comparable sensitivity to handheld pressure algometry for deep pressure pain threshold but not temporal summation of pain. SST complemented standard biopsychosocial assessment of pediatric chronic pain; use of SST may facilitate the understanding of disordered neurobiology.